Blackening the silver screen: a cinema of black consciousness in South Africa - Aiseng, Kealeboga (My University, 2017)
A positive development emerged in the early 1990s in the South African film industry when the government started to see cinema as one of the institutions to forge social cohesion in the processes of democratization and development (Botha, 2005). However, the country’s industry is still struggling with many problems such as establishing and developing the local audience for its products, domination of international films in both cinemas and television, insufficient film-funding development and paying too much attention on Hollywood standards. This dissertation critically studies the state of post-apartheid South African cinema. The main feature this study addresses is that no critical framework exists for analyzing post-apartheid film in terms of how they address or represent socio-political factors, especially factors relating to black sensibility. It is important to understand the role that filmmakers have played to incorporate issues of black sensibility in South African cinema since the end of apartheid. As a result, the author developed the first framework of its kind, referred to as a ‘cinema of Black Consciousness’. The author draws on scholarship on black emancipation, Black Consciousness, African Renaissance and Afrocentricity to develop such an analytical framework. This scholarship enhances the feasibility of a cinema of Black Consciousness not only as a South African framework, but as a framework that can be used to analyse any film that seeks to represent the socio-politico struggles of the black people. In order to test the framework, this study analysed two post-apartheid South African films, Life, Above All (2010, Oliver Schmitz), Elelwani (2012, Ntshaveni wa Luruli). The study concludes that some films produced in South African cinema introduce a film culture that seeks to represent the needs and the struggle of black people. However, a problem remains with regards to the country’s institutional structures – herein referred to as structural censorship – such as funding and distribution agencies that continue to marginalize black-centred films.
A research report submitted in fulfillment of the requirements for the degree of Masters of Arts to the Faculty of Humanities, University of the Witwatersrand, University of the Witwatersrand, Johannesburg, 2017
Keywords: Film criticism; Motion pictures--Study and teaching; Motion picture acting